The Effects of Institutional Ownership and Growth Opportunities on Malaysian Corporate Risk-Taking Behaviour - Hazwani Ahmad, Hanis; Azhari, Adilah (International Journal of Psychosocial Rehabilitation, 2020)
Purpose - This study aimed to highlight how institutional ownership could mitigate excessive corporate risk-taking. The investor may prefer high growth firm that exhibits high risk-taking. Thus, this study also examined firms’ growth and its’ effects on corporate risk-taking behaviour. Design/Methodology/Approach - Final samples for an estimation model consisted of 522 Malaysian non-financial firms selected from Bursa within 15 years from 2000 until 2014. This study utilized fixed panel regression and GMM to solve endogeneity problems. Findings - Its finding reported robust evidence that institutional ownership was negatively associated with corporate risk-taking. This study also confronted the endogeneity problem between institutional ownership, growth opportunity, and corporate risk-taking. The finding showed that institutional ownership has no causality relationship; conversely, growth opportunity has a causality relationship with corporate risk-taking. Originality/value - Most papers focused on banking and insurances paying less attention to non-financial firms, especially in the context of Malaysia as a developing country which ultimately requires better governance. This study highlighted on institutional ownership mitigate excessive risk-taking and encourage good governance through their monitoring role. In the study, the importance of growth opportunity with respect to corporate risk-taking to maximize shareholder wealth and stimulating economic development in Malaysia was highlighted. The effect of growth opportunity on corporate risk-taking exhibited mixed results.